Characterization of the stress-strain state in a gas turbine engine compressor disc taking into account damage accumulation - Natalia Boychenko; Ivan Ishtyryakov (Fracture and Structural Integrity)

(untitled)
A stress-strain state analysis of a gas turbine engine compressor disc was conducted with consideration to the accumulation of damages under various loading conditions in the temperature range. Characterization of constraint effects was performed using the local stress triaxiality h, TZ-factor and In-factors for various crack sizes and different operation conditions. The distributions of elastic, plastic and creep stress intensity factors were determined by numerical calculation. Results for several crack front positions, temperature values and disc rotation angular velocity were obtained. The differences in the behaviour of elastic and nonlinear fracture resistance parameters were observed on the basis of loading conditions, crack geometry and temperature. Nonlinear stress intensity factors are preferred as the fracture resistance parameters of materials and structures.